Brief Group Intervention Targeting Perfectionism in Adults with Anorexia Nervosa: Empirically Informed Protocol. (10th August 2016) - Tchanturia, Kate; Larsson, Eva; Adamson, James
Abstract: Objective: This study aimed to evaluate the perfectionism group intervention in adults with anorexia nervosa (AN) in an inpatient setting. Method: Adults with AN (N = 35) received six weekly sessions of the empirically informed intervention with experiential exercises. Participants' self‐reported perfectionism and satisfaction were collected pre‐group and post‐group intervention. Results: Statistically, significant differences were observed for overall perfectionism, concern over mistakes and personal standard dimensions of perfectionism. Participants found the sessions useful and felt confident in using the skills they had learnt. Conclusions: The revised perfectionism group with experiential exercises seemed to be a practical and helpful intervention for patients with AN in an inpatient programme. Copyright © 2016 John Wiley & Sons, Ltd and Eating Disorders Association.